Pollution from timber processing industries in Nigeria: challenge and adaptive measures (Agriculture, Food, and Natural Resources Journal, 2024)
Production industries process raw materials (input) and generate by-products (residues) of various forms. One of the major challenges of industrial sectors in Nigeria is pollution resulting from improperly managed and indiscriminately disposed residues. Noise produced from the use of heavy industrial machines is another major source of pollution from industrial processes. The timber industry is among the production industries in Nigeria that is renowned for its great contribution to the economy’s Gross Domestic Product (GDP). However, throughout the wood supply chain-from sawmills to final products, the wood products manufacturing industry is a potential source of environmental pollution. This paper examines viable adaptive measures in the management of air, land, noise, and water pollution with a view to addressing the challenges of environmental pollution. During sawmilling procedures, huge biomass is generated into residues (sawdust, shavings, trimmings, edgings, and so on), noise is produced from mechanical processes, and particulates are released as byproducts of fossil fuel combustion from machines and power-generating sets. In Nigeria, large volumes of residues or byproducts are indiscriminately disposed of (or improperly managed) in most timber processing industries. It is noteworthy that environmental pollution is among the challenges with far-reaching harmful effects on Nigerian citizens. And could lead to pollution-related problems, including flooding, disease outbreaks, pandemics, health hazards, and death. The identified pollution-related challenges from timber industries in Nigeria and their associated consequences can be drastically reduced if conscious efforts are put in place. Hence, this study recommended the reconstitution of timber residues.
Keywords: Agro-allied; Nigeria; Petrochemical; Sawdust